(untitled) (Sains Humanika, 2008)
Empirical research on emotional intelligence has uncovered the relationship between emotional intelligence and students’ behavior. Concomitantly, reports in the media regarding events that are related to emotional outburst among the students raised an issue about students’ level of emotional intelligent. This study aims to identify emotional intelligence quotient among secondary school students. Additionally, this study also aims to describe their emotional intelligence profile. Sample of the study consisted of 513 form two and form four students from four schools in Selangor and Negeri Sembilan. Malaysian Emotional Quotient Inventory for adolescene (MEQI–A) was administered to determine the emotional quotient of the respondent. The EQ index was calculated based on the seven domains and ranging from 0 – 100 to describe individual’s emotional intelligence. Results of the study showed emotional intelligence index of the respondents at 76.02 that is in the lower part of the fourth quartile. The emotional intelligence profile for the whole sampel showed respondents scored less than 75 percent in three domains namely the domain of self–regulation, social skills and self awareness. Thus, these domains should be addressed accordingly in order to increase students’ emotional intelligence as a whole. This paper also reported the profile of emotional intelligence according to form, gender and school location.